Creating the European External Action Service: Preconditions for avoiding a rude awakening - Julia Lieb; Andreas Maurer (Stiftung Wissenschaft und Politik (SWP), 2008)
The Lisbon Treaty provides for the establishment of a European External Action Service (EEAS), which has tremendous potential for making European foreign policy both more coherent and more effective. However, if the EEAS is to be more than a paper tiger, forceful efforts to pave the way for its establishment must be made in good time. There are two key priorities here: firstly, to make sure that a core EEAS staff will be able to work effectively once the Lisbon Treaty enters into force, which could happen on 1 January 2009; and secondly, to ensure that a pragmatic plan for the EEAS's future establishment and continued development guarantees its long-term success
Keywords: 320